30-day outcome after orthopaedic surgery in patients assessed as negative for COVID-19 at the time of surgery during the peak of the pandemic. (August 2020) - Price, Andrew; Shearman, Alexander D.; Hamilton, Thomas W.; Alvand, Abtin; Kendrick, Ben; ,
Abstract : Introduction: The aim of this study is to report the 30 day COVID-19 related morbidity and mortality of patients assessed as SARS-CoV-2 negative who underwent emergency or urgent orthopaedic surgery in the NHS during the peak of the COVID-19 pandemic. Method: A retrospective, single centre, observational cohort study of all patients undergoing surgery between 17 March 2020 and 3May 2020 was performed. Outcomes were stratified by British Orthopaedic Association COVID-19 Patient Risk Assessment Tool. Patients who were SARS-CoV-2 positive at the time of surgery were excluded. Results: Overall, 96 patients assessed as negative for SARS-CoV-2 at the time of surgery underwent 100 emergency or urgent orthopaedic procedures during the study period. Within 30 days of surgery 9.4% of patients (n = 9) were found to be SARS-CoV-2 positive by nasopharyngeal swab. The overall 30 day mortality rate across the whole cohort of patients during this period was 3% (n = 3). Of those testing positive for SARS-CoV-2 66% (n = 6) developed significant COVID-19 related complications and there was a 33% 30-day mortality rate (n = 3). Overall, the 30-day mortality in patients classified as BOA low or medium risk (n = 69) was 0%, whereas in those classified as high or very high risk (n = 27) it was 11.1%. Conclusion: Orthopaedic surgery in SARS-CoV-2 negative patients who transition to positive within 30 days of surgery carries a significant risk of morbidity and mortality. In lower risk groups, the overall risk of becoming SARS-CoV-2 positive, and subsequently developing a significant postoperative related complication, was low even during the peak of the pandemic. In addition to ensuring patients are SARS-CoV-2 negative at the time of surgery it is important that the risk of acquiring SARS-CoV-2 is minimized through their recovery. Cite this article: Bone Joint Open 2020;1-8:474–480.